The Effect of Using the Interactive Board (IB) as an Educational Instrument on 11th Grade Students’ Achievement in Physics and their Attitudes Towards its Use - Alqawasmi, Abdellateef; Alsalhi, Najeh Rajeh; Alarabi , Khaleel; Alabidi , Suzan (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aimed to examine the effect of the interactive board (IB) as an educational instrument on 11th Grade Students’ achievement in physics and their attitudes towards its use. Methods: The study was conducted using a quasi-experimental design case study. The researchers used an achievement test as well as an attitude survey consisting of (23) IB-relevant items covering three domains: student involvement and motivation, learning and teaching, and interactive board limitations. The study sample comprised (63) purposefully selected eleventh-grade students’ (31 students as a control group and 32 as an experimental group) from the first term of the scholastic year 2021-2022. Results: The study results showed that the students in the experimental group who were taught using the interactive board outperformed the students in the control group who were taught using the traditional board in terms of academic achievement. The results also revealed positive attitudes among students towards the interactive board. Conclusions: The use of interactive board as a teaching tool has a positive effect on increasing students' achievement in physics, in addition to their acceptance of its use. As a result, the study recommends conducting further research on the use of interactive board across different school levels.